'Happy, excited, terrified' feelings from the floor: a phenomenological inquiry into the lived experiences of nurses who transition from student to registered nurse. (November 2022) - Hardiman, Michele; Watkin, Judy; Barbosa, Hector Belmonte
No abstract available